Tetrachlorobisphenol A and bisphenol AF induced cell migration by activating PI3K/Akt signaling pathway via G protein‐coupled estrogen receptor 1 in SK‐BR‐3 cells. Issue 1 (3rd October 2022) - Yu, Mengjie; Xu, Lanbing; Lei, Bingli; Sun, Su; Yang, Yingxin
Abstract: Different subtypes of breast cancer express positively G protein‐coupled estrogen receptor 1 (GPER1). Our previous studies found that tetrachlorobisphenol A (TCBPA) and bisphenol AF (BPAF) significantly promoted SK‐BR‐3 cell proliferation by activating GPER1‐regulated signals. The present study further investigated the effects of TCBPA and BPAF on the migration of SK‐BR‐3 cells and examined the role of phosphatidylinositol 3‐kinase‐protein kinase B (PI3K/Akt) and its downstream signal targets in this process. We found that low‐concentration BPAF and TCBPA markedly accelerated the migration of SK‐BR‐3 cells and elevated the mRNA levels of target genes associated with PI3K/Akt and mitogen‐activated protein kinase (MAPK) signals. TCBPA‐ and BPAF‐induced upregulation of target genes was significantly reduced by GPER1 inhibitor G15, the PI3K/Akt inhibitor wortmannin (WM), and the epidermal growth factor receptor (EGFR) inhibitor ZD1839 (ZD). G15 and WM also decreased cell migration induced by TCBPA and BPAF. The findings revealed that TCBPA and BPAF promoted SK‐BR‐3 cell migration ability by activating PI3K/Akt signaling pathway via GPER1‐EGFR.